Job satisfaction among academic and non-academic staff in public universities in Malaysia: A review - Noorshella Che Nawi; Mohammad Ismail; Mohd Asrul Hery Ibrahim; Nursalihah Ahmad Raston; Zaminor Zamzamir Zamzamin; Azila Jaini (Canadian Center of Science and Education, 2016)
Many previous studies have solely focused on measuring job satisfaction in one category only either among academic or non-academic staff. However, in an educational institution, the two categories of workforce work hard in developing the university. Hence, it is crucial to measure the level of satisfaction in these jobs. Taking this into account, this study intends to identify the factors that contribute to job satisfaction among academic and non-academic staff in public universities. This study adapts the research frameworks from Lacy and Sheehan (1997), and Smerek and Peterson (2006) to measure job satisfaction among academic and non-academic staff, respectively.